Mosses as spore traps for myxomycetes - Stephenson, Steven L. (2020)
Small-mesh nylon bags filled with autoclaved samples of mosses were placed out in the field in northwest Arkansas and central Costa Rica to assess the extent to which mosses could serve as spore traps for myxomycetes. The bags were suspended from low hanging tree branches and left in place for more than four months. When the bags were recollected, the mosses were processed for myxomycetes using the moist chamber culture technique. Thirty-eight (95 %) of the moist chamber cultures prepared with samples of bryophytes from bags placed out in Costa Rica were positive for myxomycetes, and 36 (90 %) of these cultures produced fruiting bodies. In contrast, only 28 (70 %) of the moist chamber cultures prepared with samples of bryophytes placed out in northwest Arkansas were positive for myxomycetes, and just 7 (18 %) of these produced fruiting bodies. Sixteen species in eight genera were represented among the 98 specimens appearing in both sets of cultures. Clearly, mosses are effective at trapping airborne spores of myxomycetes